Facing financial barriers to healthcare: patient-informed adaptation of a conceptual framework for adults with a history of cancer - Biddell, Caitlin B.; Waters, Austin R.; Angove, Rebekah S. M.; Gallagher, Kathleen D.; Rosenstein, Donald L.; Spees, Lisa P.; Kent, Erin E.; Planey, Arrianna Marie; Wheeler, Stephanie B. (Frontiers in Psychology, 2023)
Background: Cancer-related financial hardship is associated with negative clinical outcomes, which may be partially explained by cost-related delayed or forgone care in response to financial barriers. We sought to understand patient experiences facing financial barriers to medical care following a cancer diagnosis. Methods: We conducted virtual, semi-structured interviews in Fall 2022 with 20 adults with a history of cancer who had experienced cancer-related financial hardship in the prior year. We used template analysis within a pragmatic paradigm, combining constructivist and critical realist theoretical perspectives, to analyze interview transcripts and adapt an existing conceptual framework of financial barriers to care. Results: The majority of interviewees identified as women (70%), non-Hispanic white (60%), and reported an annual household income of <48,000 (60%). As interviewees sought to overcome financial barriers, they described substantial frustration at the limitations and complexities of US health and social care systems, resulting in a reliance on a fragmented, uncertain resource landscape. The administrative burden resulting from bureaucratic systems and the advocacy responsibilities required to navigate them ultimately fell on interviewees and their caregivers. Thus, participants described their ability to overcome financial barriers as being influenced by individual and interpersonal factors, such as social support, comfort asking for help, time, prior experience navigating resources, and physical and mental health. However, participants noted health system organizational factors, such as whether all new patients proactively met with a social worker or financial navigator, as having the potential to lessen the administrative and financial burden experienced. Conclusions: We present an adapted conceptual framework outlining multi-level factors influencing patient experiences coping with financial barriers to medical care. In addition to influencing whether a patient ultimately delays or forgoes care due to cost, financial barriers also have the potential to independently affect patient mental, physical, and financial health.